2014
DOI: 10.1371/journal.pcbi.1003831
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of ATP as an Allosteric Modulator

Abstract: Adenosine-5’-triphosphate (ATP) is generally regarded as a substrate for energy currency and protein modification. Recent findings uncovered the allosteric function of ATP in cellular signal transduction but little is understood about this critical behavior of ATP. Through extensive analysis of ATP in solution and proteins, we found that the free ATP can exist in the compact and extended conformations in solution, and the two different conformational characteristics may be responsible for ATP to exert distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 72 publications
1
45
0
Order By: Relevance
“…S4). This conformation is characteristic of regulatory ATP molecules, whereas substrate ATP molecules are extended (35). The bound ATP is accompanied by a magnesium ion, and the O2A and O2B atoms of the ATP molecule provide two of the six ligands; the other four are almost certainly unresolved water molecules.…”
Section: Resultsmentioning
confidence: 97%
“…S4). This conformation is characteristic of regulatory ATP molecules, whereas substrate ATP molecules are extended (35). The bound ATP is accompanied by a magnesium ion, and the O2A and O2B atoms of the ATP molecule provide two of the six ligands; the other four are almost certainly unresolved water molecules.…”
Section: Resultsmentioning
confidence: 97%
“…In PRS, we introduce perturbations by applying a random external unit force on single residues as a first-order approximation to the forces exerted on a protein in a crowded cell environment, then we analyze the residue response fluctuation profile of the rest of the chain using linear response theory. It has been shown that PRS using an elastic network model or coupled with MD can be useful to 1) obtain conformational changes upon binding (22,41); 2) identify critical residues that mediate long-range communication through dynamic allostery (10,65,(68)(69)(70); 3) predict a better binding affinity score through rapidly generating an ensemble of configurations for flexible docking (71)(72)(73); and 4) distinguish diseaseassociated and putatively neutral population variations in human proteome (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence indicates that ATP can also function as an allosteric modulator (Huang et al, 2014;Lu et al, 2014a). Thus, understanding the allosteric mechanism of ATP in Akt1 may provide broader insights into the role of ATP and its mechanism as an endogenous modulator in cell signaling and in an important class of enzymes (Nussinov and Tsai, 2013;Lu et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%